As reformas universitárias no contexto do Iluminismo Católico (séc. XVIII): uma modernização "moderada" nas Universidade de Coimbra e de Salamanca? - Alves, Carlos Fernando Teixeira (Lusitania sacra, 2024)
In this article we intend to make a comparative approach to the reforms of the Universities of Salamanca and Coimbra, in the second half of the 18th century, influenced by the Catholic Enlightenment. Starting from the hypothesis that this Catholic background forced the adoption strategies of ideas that circulated in the European space, we intend to identify in a comparative way the adoption of pedagogical and scientific ideas in the curricular construction, but also in the adoption of new works for the classes. Seeking, also, to establish parallels with the general lines that characterized other university reforms in Europe.